2015
DOI: 10.1097/opx.0000000000000511
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Normal Corneal Shape and the Influence of Eyelid Morphometry

Abstract: Sectorial variation is present in normal corneal shape and this variation is not significantly different between East and non-East Asian eyes. Several eyelid features appear to influence corneal shape in primary gaze.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…Our results differ from those of many reports investigating Western children [ 4 6 , 16 , 17 ]. Maseedupally et al found that several eyelid morphometry appear to influence corneal shape in primary gaze and horizontal palpebral fissure width and upperlid curvature can affect corneal spherical equivalent with difference between ethnicities [ 18 ]. This might be due to anatomical morphometrical differences in Korean children, including more puffy eyelids and a more prominent epicanthal fold than Western children.…”
Section: Discussionmentioning
confidence: 99%
“…Our results differ from those of many reports investigating Western children [ 4 6 , 16 , 17 ]. Maseedupally et al found that several eyelid morphometry appear to influence corneal shape in primary gaze and horizontal palpebral fissure width and upperlid curvature can affect corneal spherical equivalent with difference between ethnicities [ 18 ]. This might be due to anatomical morphometrical differences in Korean children, including more puffy eyelids and a more prominent epicanthal fold than Western children.…”
Section: Discussionmentioning
confidence: 99%
“…Most notable was a significantly greater degree of mid‐peripheral corneal flattening in the superior‐nasal region of East Asian eyes, at the approximate location of the superior nasal eyelid margin, along with a larger increase in negative vertical coma. It has been well documented that East Asian eyes typically display narrower vertical palpebral apertures (with the upper eyelid substantially closer to the corneal centre) along with a steeper upper lid angle compared to Caucasian eyes . These ethnic anatomical differences in the upper eyelid, or the tightness/tension of the eyelid, may explain the differences observed in the corneal optics.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that East Asian eyes typically display narrower vertical palpebral apertures (with the upper eyelid substantially closer to the corneal centre) along with a steeper upper lid angle compared to Caucasian eyes. 24,25 These ethnic anatomical differences in the upper eyelid, or the tightness/tension of the eyelid, may explain the differences observed in the corneal optics. However, since central corneal clearance was maintained during lens wear (based on OCT imaging), eyelid forces do not appear to simply mechanically compress the posterior lens surface against the cornea, but perhaps results in tighter peripheral seal off and altered post-lens tear layer fluid dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these patients, 70% had significant refractive error, 43% had astigmatism of more than 1.0 D, 55% had anisometropia of more than 1.25 D sphere or 0.75 D cylinder, 27.5% had strabismus, and 50% had amblyopia 18 . In cases of unilateral Ptosis, the drooping eye has more amblyogenic refractive error than the normal eye 19,20 .…”
Section: Resultsmentioning
confidence: 99%